Predictors of follow-up non-compliance after definitive radiotherapy for locally advanced cervical cancer at a community cancer center - Lucas G. Sapienza; Justin J. Thomas; Alfredo E. Echeverria; Shelly Sharma; Daniel A. Hamstra; Tracilyn R. Hall; Michelle S. Ludwig (Elsevier, 2022)
Introduction: Non-compliance to post-treatment cancer surveillance can lead to late detection of recurrence. This study aims to identify patients at high risk for loss of follow-up after radiotherapy for locally advanced cervical cancer. Methods: Consecutive patients with locally advanced cervical cancer treated with definitive chemoradiotherapy (2013-2020) at a community cancer center were retrospectively reviewed. The main outcome was overall follow-up compliance rate over time. Additionally, specialist-specific follow-up times, reasons for discontinuation and predictors of loss of follow-up events were evaluated. Results: The median age of the 154 patients included was 46.5 years (range: 26-84). The 6-month, 1-, 3-, and 5-year overall loss of follow-up rates were: 5.3%, 15.3%, 33.6%, and 48.2%, respectively. After a median overall follow-up time of 21.0 months, the median specialist-specific surveillance times were 17 months and 6 months with gynecologic and radiation oncologists, respectively (p < 0.01). Overall, the most common reasons for loss of follow-up were financial (21.7%) and relocation to another city (28.3%). By specialty, the most common reasons were relocation of care (56.5%, gynecologic oncologist) and disease progression (31.3%, radiation oncologist). In the multivariable analysis, older age (continuous, OR: 0.96; p < 0.01) and Hispanic ethnicity (OR: 0.39; p < 0.01) were protective against loss of follow-up, while increased number of gestations (continuous, OR: 1.23, p = 0.01) and living farther from the cancer center (continuous, OR: 1.002; p = 0.03) increased the chance of loss of follow-up. Conclusion: Younger, non-Hispanic, multiparous women that live far from the community cancer center have an increased chance of follow-up discontinuity, which are attributed to financial reasons in more than 20% of the cases.